The analysis of the effects of income inequalities on the at-risk-of-poverty rate in the European Union - Maria Berta BELU; Silvana BOBÂRNAT (CRIVOI); Maria Denisa VASILESCU; Eva MILITARU (Theoretical and Applied Economics, 2024)

(untitled)
Poverty is a challenge for all countries and its eradication is a common goal in the European Union. Our paper analyses the statistical and theoretical relationship between social inequalities and the at-risk-of-poverty rate. For a holistic understanding of the poverty phenomenon in the EU, other variables such as economic growth, social protection expenditure, and the old-age dependency ratio were also included in the analysis. The methodology is based on panel data models. A regression model was built with data for the period 2011-2022, for the 27 EU countries. The econometric model of the at-risk-of-poverty rate highlighted a series of factors, among which the Gini coefficient is one of the most influential. Other important factors were research and development expenditure, social protection expenditure, GDP per capita, the unemployment rate, and the old-age dependency ratio. The cluster analysis grouped the EU countries into three clusters. Understanding the phenomenon of poverty is a prerequisite for alleviating it, generating social solidarity, and rebuilding a fairer society. Our research contributes to the evaluation of the interaction between inequalities and poverty in Romania and the EU.